Preparation method and application of iron-doped polymer self-assembled nanoparticles

By mixing non-conjugated polyimide and trivalent iron salt in the solvent, and preparing iron-doped polymer nanoparticles through self-assembly technology, the existing semiconductor photocatalysts have been solved, and efficient and stable photocatalytic degradation effects are achieved.

CN119798688APending Publication Date: 2025-04-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311315531.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When removing organic pollutants in water, existing semiconductor photocatalysts have disadvantages such as easy agglomeration, low photo conversion efficiency and difficulty in separation in the future, which limits their application scope.

Method used

Iron-doped polymer self-assembled nanoparticles were prepared by mixing the non-conjugated polyimide with the trivalent iron salt in a solvent, stirring, and precipitating and drying. This method uses self-assembly technology to bring iron ions into the nanoparticles to form nanoparticles with catalytic oxidation properties.

Benefits of technology

It has achieved rapid degradation of organic pollutants, stable structure, high photocatalytic degradation efficiency, and no need to add other light sources. It is suitable for photocatalytic degradation, biosensing, biomedicine and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798688A_ABST
    Figure CN119798688A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of iron-doped polymer self-assembled nanoparticles, and the preparation method comprises the following steps: (1) mixing non-conjugated polyimide, trivalent iron salt and a first solvent, and stirring to form a first solution; and (2) adding a second solvent into the first solution, precipitating and drying to obtain the iron-doped polymer self-assembled nanoparticles, the molecular weight of the non-conjugated polyimide is less than or equal to 15000Da. The method has the characteristics of simple synthesis, high product yield, low cost, high purity and the like, and has huge application prospects in the fields of photocatalytic degradation, photothermal therapy, bacteria resistance and bacteriostasis and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method of iron-doped polymer self-assembled nanoparticles and application thereof, belonging to the field of energy nanomaterials. Background Art

[0002] The increasingly serious environmental pollution problem has attracted great attention from people. Organic pollutants (OPs) are one of the main sources of environmental pollution, which greatly harms people's health, such as immunotoxicity, neurotoxicity, carcinogenicity and other toxicities. Therefore, the efficient removal of organic pollutants in water is of great significance to ecology and environment. At present, the photocatalytic technology of semiconductor photocatalysts can reduce most organic pollutants in wastewater into biologically treatable forms or less toxic organic compounds. Some can even decompose organic pollutants into CO2, H2O, NO3 - PO4 3- and small molecules such as halogen ions. However, these semiconductor materials often have disadvantages such as easy aggregation, low efficiency of light conversion and difficulty in subsequent separation, which limits their application range. Therefore, exploring new functional materials with simple synthesis, high yield and efficient degradation has become a new research hotspot.

[0003] Multifunctional iron-doped polymer self-assembled nanoparticles are an emerging functional material that greatly improves catalytic oxidation performance by exposing more active sites, thereby achieving rapid degradation of organic pollutants. Self-assembly refers to the spontaneous formation of a structure with unique characteristics through intermolecular forces, so that individual molecules form a directional and ordered structure. The primitives are orderly connected through non-covalent bonds to form an assembly with a specific structure or function, which has shown great application potential in the fields of biomedicine and environmental testing. On the one hand, the polymer chain of iron-doped polymer self-assembled nanoparticles can self-assemble through the interaction of hydrogen bonds and van der Waals forces, bringing iron ions into the self-assembly, improving the stability of metal materials and enhancing the activity of metal centers; on the other hand, electron delocalization can occur in the excited state, and the generated free radicals (superoxide anion radicals, hydroxyl radicals, etc.) can be captured by trivalent iron ions and reduced to divalent iron ions to form a Fenton-like catalytic oxidation system, achieving the degradation of organic pollutants near the nanoparticles. Therefore, iron-doped polymer self-assembled nanoparticles have great application value in the fields of photocatalytic degradation, biosensing, biomedicine, food safety, and environmental engineering. Summary of the invention

[0004] According to one aspect of the present application, a method for preparing iron-doped polymer self-assembled nanoparticles having catalytic degradation performance is provided, the preparation method comprising:

[0005] (1) mixing a non-conjugated polyimide, a trivalent iron salt and a first solvent, and stirring to form a first solution;

[0006] (2) adding a second solvent to the first solution, precipitating, and drying to obtain the iron-doped polymer self-assembled nanoparticles;

[0007] The average molecular weight of the non-conjugated polyimide is ≤15000Da.

[0008] Optionally, the average molecular weight of the non-conjugated polyimide is 7000-15000 Da.

[0009] Optionally, the molecular weight of the non-conjugated polyimide is independently selected from any value among 1000Da, 2000Da, 3000Da, 4000Da, 5000Da, 6000Da, 7000Da, 7500Da, 8000Da, 9000Da, 10000Da, 11000Da, 12000Da, 13000Da, 14000Da, 15000Da or a range between any two of the above.

[0010] Optionally, the non-conjugated polyimide is selected from at least one of polyethylene oxalic acid diimide, polyethylene glutaric acid diimide, polyphenyl glutaric acid diimide, polyethylene succinic acid diimide, polyphenyl succinic acid diimide, and poly-N-ethyl-2-carboxymethylimide-succinimide;

[0011] The non-conjugated polyimide is prepared from a mixture containing alkane polycarboxylic acid and polyamine by melt polymerization under an inert atmosphere.

[0012] In the present application, the alkane polycarboxylic acid is selected from at least one of oxalic acid, trisaccharic acid, glutaric acid, and succinic acid, but is not limited to the above substances.

[0013] In the present application, the polyamine is selected from at least one of ethylenediamine and phenylenediamine, but is not limited to the above substances.

[0014] Optionally, the trivalent iron salt is selected from at least one of ferric chloride, ferric nitrate and ferric sulfate.

[0015] Optionally, the mass ratio of the non-conjugated polyimide to the trivalent iron salt is 1:0.1-20.

[0016] Optionally, the mass ratio of the non-conjugated polyimide to the trivalent iron salt is independently selected from any value of 1:0.1, 1:1, 1:2, 1:4, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20 or a range between any two of the above.

[0017] Optionally, the first solvent is selected from at least one of dimethyl sulfoxide, methanol, ethanol, water and dichloromethane.

[0018] Optionally, the second solvent is selected from at least one of ethanol, chloroform, tetrahydrofuran, acetonitrile and toluene.

[0019] Optionally, the stirring time is 30 to 60 minutes.

[0020] Optionally, the stirring time is independently selected from any value among 30 min, 40 min, 50 min, 60 min or a range between any two of the above.

[0021] Optionally, the drying temperature is 40-70°C.

[0022] Optionally, the stirring time is independently selected from any value of 40°C, 50°C, 60°C, 70°C or a range between any two of the above values.

[0023] Optionally, the drying time is 5 to 10 hours.

[0024] Optionally, the stirring time is independently selected from any value among 5h, 6h, 7h, 8h, 9h, 10h or a range between any two of the above.

[0025] As a specific embodiment, the preparation method comprises the following steps:

[0026] (1) dispersing a low molecular weight non-conjugated polyimide having a self-assembly function and a carboxylic acid group as a side group and a capping group and a trivalent iron salt in a first solvent and uniformly stirring;

[0027] (2) gradually adding a second solvent until a precipitate is produced, filtering the precipitate and drying it, thereby obtaining iron-doped polymer self-assembled nanoparticles with catalytic degradation performance;

[0028] The low molecular weight self-assembled non-conjugated polyimide described in step (1) can be prepared by melt polymerization assisted by inert gas purging using alkane polycarboxylic acid and polyamine, and the molecular weight is not more than 15000Da.

[0029] Another aspect of the present application provides an application of the iron-doped polymer self-assembled nanoparticles obtained by the above preparation method in the degradation of methylene blue.

[0030] Optionally, the application includes: adding H2O2 solution to a solution containing the iron-doped polymer self-assembled nanoparticles and methylene blue to react.

[0031] In the present application, the preparation method of iron-doped polymer self-assembled nanoparticles with catalytic degradation performance is based on the principle that trivalent iron ions can be fixed by interacting with low molecular weight polyimide and carbonyl groups on carboxylic acid side groups, and non-conjugated polymerized imide self-assembles to form nanoparticles under hydrogen bonding or van der Waals force interaction, bringing iron ions into the interior of the particles; at the same time, the hydroxyl radicals produced by non-conjugated polymerized imide stimulating H2O2 can be captured by iron metal ions, and part of the trivalent iron ions are reduced to divalent iron ions, resulting in the simultaneous presence of divalent iron, trivalent iron and hydroxyl radicals in the nanoparticles, forming catalytic oxidation nanoparticles with Fenton-like properties. This method has the characteristics of simple synthesis, high product yield, low cost, high purity, etc., and has great application prospects in the fields of photocatalytic degradation, photothermal therapy, antibacterial and antibacterial.

[0032] The beneficial effects of this application include:

[0033] (1) The preparation method is simple, low cost, short cycle and high yield;

[0034] (2) | The iron-doped polymer self-assembled nanoparticles have a stable structure and can oxidize the colorless 3,3′,5,5′-tetramethylbenzidine hydrochloride aqueous solution into blue;

[0035] (3) No other light source is required during degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a comparison spectrum of fluorescence changes of iron-doped polyethylene oxalic acid diimide in Example 1 of the present application;

[0037] Figure 2 This is the UV absorption spectrum of polyethylene oxalic acid diimide in Example 1 of the present application;

[0038] Figure 3 The XRD pattern of polyethyl oxalic acid diimide in Example 1 of the present application;

[0039] Figure 4 The XRD spectrum of iron-doped polyethylene oxalic acid diimide in Example 1 of the present application;

[0040] Figure 5 This is a process diagram of the degradation of methylene blue by iron-doped polyethylene oxalate diimide in Example 1 of the present application. DETAILED DESCRIPTION

[0041] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0042] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0043] In the embodiments of the present application, the fluorescence spectrum testing instrument is a fluorescence spectrophotometer, and the testing conditions are a voltage of 400 V and a slit of 5 nm;

[0044] The instrument used for the UV absorption spectrum test is a UV spectrophotometer, and the test conditions are a test range of 200-700nm;

[0045] The instrument used for the XRD spectrum test is an X-ray diffractometer, and the test conditions are a scanning angle of 20-90°.

[0046] Example 1

[0047] (1) 0.09 g of oxalic acid and 0.07 g of ethylenediamine were ground and mixed, and then calcined in a tube furnace at 200° C. for 3 h.

[0048] (2) 0.6 g of poly(ethyl oxalic acid diimide) with an average molecular weight of 7000 Da was dissolved in 6 mL of dimethyl sulfoxide (DMSO) at room temperature, and ultrasonicated for 10 min. Then, 0.6 g of ferric chloride hexahydrate was added and stirred for 30 min. Then, 50 mL of ethanol was added to produce a precipitate. The precipitate was filtered and vacuum dried at 60 ° C for 6 h to obtain iron-doped poly(ethyl oxalic acid diimide) self-assembled nanoparticles with catalytic degradation performance. The yield was 68%. 2 mg of the nanoparticles were added to 2 mL of 1 mg / mL methylene blue solution, and then diluted H2O2 solution (final volume was 1 mmol / L) was added. The blue solution turned into a colorless solution in 5 to 20 seconds.

[0049] Figure 1 The fluorescence change comparison spectrum of the iron-doped polyethylene oxalic acid diimide prepared in this example is as follows: Figure 1 It can be seen that the fluorescence becomes significantly weaker after iron doping.

[0050] Figure 2 For the ultraviolet absorption spectrum of polyethyl oxalic acid diimide in this embodiment, Figure 2 It can be seen that a strong absorption band appears around 260nm.

[0051] Figure 3 For the XRD pattern of polyethyl oxalic acid diimide in this embodiment, Figure 3 It can be seen that a peak appears at about 18°.

[0052] Figure 4 The XRD pattern of the iron-doped polyethylene oxalic acid diimide prepared in this embodiment is as follows: Figure 4 It can be seen that it becomes wider and larger after iron doping, which may be because the structure becomes more disordered after iron doping.

[0053] Figure 5The degradation process of the iron-doped polyethylene oxalic acid diimide prepared in this example is shown in FIG. Figure 5 It can be seen that as time increases, the absorbance continues to decrease, indicating that the degradation effect of methylene blue is better.

[0054] Example 2

[0055] (1) 0.13 g of glutaric acid and 0.13 g of p-phenylenediamine were ground and mixed and then calcined at 200° C. in a tube furnace for 3 h.

[0056] (2) 0.5 g of poly(ethyl glutaric acid diimide) with an average molecular weight of 7000 Da was dissolved in 6 mL of methanol at room temperature, ultrasonicated for 10 min, then 0.5 g of ferric nitrate was added and stirred for 30 min, then 50 mL of chloroform was added to produce precipitation, the precipitate was filtered and vacuum dried at 60 ° C for 7 h, and iron-doped poly(ethyl glutaric acid diimide) self-assembled nanoparticles with catalytic degradation performance were obtained, with a yield of 69%. 2 mg of the nanoparticles were added to 2 mL of 1 mg / mL methylene blue solution, and then diluted H2O2 solution (final volume was 1 mmol / L) was added, and the blue solution became colorless within 5-20 seconds.

[0057] Example 3

[0058] (1) 0.13 g of glutaric acid and 0.13 g of m-phenylenediamine were ground and mixed and then calcined in a tube furnace at 200° C. for 3 h.

[0059] (2) 0.5 g of polyphenyl glutaric acid diimide with an average molecular weight of 7000 Da was dissolved in 6 mL of ethanol at room temperature, ultrasonicated for 10 min, then 0.5 g of ferric sulfate was added and stirred for 30 min, then 50 mL of tetrahydrofuran was added to produce precipitation, the precipitate was filtered and vacuum dried at 60 ° C for 6 h, and iron-doped polyphenyl glutaric acid diimide self-assembled nanoparticles with catalytic degradation performance were obtained, with a yield of 71%. 2 mg of the nanoparticles were added to 2 mL of 1 mg / mL methylene blue solution, and then diluted H2O2 solution (final volume was 1 mmol / L) was added, and the blue solution became a colorless solution within 5-20 seconds.

[0060] Example 4

[0061] (1) 0.19 g of succinic acid and 0.07 g of ethylenediamine were ground and mixed and then calcined in a tube furnace at 200° C. for 3 h.

[0062] (2) Dissolve 0.5 g of poly(ethyl succinic acid diimide) with an average molecular weight of 7000 Da in 6 mL of water at room temperature, ultrasonicate for 10 min, then add 0.5 g of ferric chloride hexahydrate and continue stirring for 30 min, then add 50 mL of acetonitrile to produce precipitation, filter the precipitate and vacuum dry it at 60 ° C for 6 h, and you can get iron-doped poly(ethyl succinic acid diimide) self-assembled nanoparticles with catalytic degradation performance, the yield is 72%. Take 2 mg of the nanoparticles and add them to 2 mL of 1 mg / mL methylene blue solution, then add diluted H2O2 solution (final volume is 1 mmol / L), and the blue solution can be turned into a colorless solution within 5-20 seconds.

[0063] Example 5

[0064] (1) 0.19 g of succinic acid and 0.07 g of ethylenediamine were ground and mixed and then calcined in a tube furnace at 200° C. for 3 h.

[0065] (2) 0.3 g of poly(ethyl succinic acid diimide) with an average molecular weight of 7000 Da was dissolved in 6 mL of dichloromethane at room temperature, and ultrasonicated for 10 min. Then, 0.6 g of ferric chloride hexahydrate was added and stirred for 30 min. Then, 50 mL of toluene was added to produce a precipitate. The precipitate was filtered and vacuum dried at 60 ° C for 7 h to obtain iron-doped poly(ethyl succinic acid diimide) self-assembled nanoparticles with catalytic degradation performance. The yield was 68%. 2 mg of the nanoparticles were added to 2 mL of 1 mg / mL methylene blue solution, and then diluted H2O2 solution (final volume was 1 mmol / L) was added. The blue solution turned into a colorless solution within 5-20 seconds.

[0066] Example 6

[0067] (1) 0.18 g of trisaccharic acid and 0.07 g of ethylenediamine were ground and mixed, and then calcined in a tube furnace at 200°C for 3 h.

[0068] (2) 0.4 g of poly (N-ethyl-2-carboxymethylimide-succinimide) with an average molecular weight of 7000 Da was dissolved in 5 mL of dimethyl sulfoxide (DMSO) at room temperature, and ultrasonicated for 10 min. Then, 0.4 g of ferric chloride hexahydrate was added and stirred for 30 min. Then, 50 mL of acetonitrile was added to produce precipitation. The precipitate was filtered and vacuum dried at 60 ° C for 7 h to obtain iron-doped poly (N-ethyl-2-carboxymethylimide-succinimide) self-assembled nanoparticles with catalytic degradation performance. The yield was 69%. 2 mg of the nanoparticles were added to 2 mL of 1 mg / mL methylene blue solution, and then diluted H2O2 solution (final volume was 1 mmol / L) was added. The blue solution turned into a colorless solution within 5-20 seconds.

[0069] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing iron-doped polymer self-assembled nanoparticles, characterized in that: The preparation method comprises: (1) mixing a non-conjugated polyimide, a trivalent iron salt and a first solvent, and stirring to form a first solution; (2) adding a second solvent to the first solution, precipitating, and drying to obtain the iron-doped polymer self-assembled nanoparticles; The average molecular weight of the non-conjugated polyimide is ≤15000Da.

2. The preparation method according to claim 1, characterized in that: The average molecular weight of the non-conjugated polyimide is 7000-15000 Da.

3. The preparation method according to claim 1, characterized in that: The non-conjugated polyimide is selected from at least one of polyethylene oxalic acid diimide, polyethylene glutaric acid diimide, polyphenyl glutaric acid diimide, polyethylene succinic acid diimide, polyphenyl succinic acid diimide, and poly-N-ethyl-2-carboxymethylimide-succinimide; The non-conjugated polyimide is prepared from a mixture containing alkane polycarboxylic acid and polyamine by melt polymerization under an inert atmosphere.

4. The preparation method according to claim 1, characterized in that: The ferric iron salt is selected from at least one of ferric chloride, ferric nitrate and ferric sulfate.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the non-conjugated polyimide to the trivalent iron salt is 1:0.1-20.

6. The preparation method according to claim 1, characterized in that: The first solvent is selected from at least one of dimethyl sulfoxide, methanol, ethanol, water and dichloromethane.

7. The preparation method according to claim 1, characterized in that: The second solvent is selected from at least one of ethanol, chloroform, tetrahydrofuran, acetonitrile and toluene.

8. The preparation method according to claim 1, characterized in that: The stirring time is 30 to 60 minutes; The drying temperature is 40-70°C; The drying time is 5 to 10 hours.

9. Use of the iron-doped polymer self-assembled nanoparticles obtained by the preparation method according to any one of claims 1 to 8 in the degradation of methylene blue.

10. The use according to claim 9, characterized in that: The application comprises: adding H2O2 solution into a solution containing the iron-doped polymer self-assembled nanoparticles and methylene blue, and reacting.

Citation Information

Patent Citations

  • Metal ion mediated chiral polyamide material and preparation method thereof

    CN112341620A

  • Novel iron-based nano material and application thereof

    CN114259474A